The Effect of Compensation on the Performance of Honorary Teachers at SMP Negeri 3 Awangpone - Fitriani, Fitriani; Irmayani, Risma; Sunita, Sunita; Arsantika, Arsantika; Dyta Sari, Putri (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2024)
The main problem in this research is 1) How to provide compensation in SMPN 3 Awangpone District Bone Regency. 2) How is the performance of the honorary teacher in SMPN 3 Awangpone District Bone Regency. 3) How is the effect of giving compensation to the improvement of the performance of honorary teachers in SMPN 3 Awangpone District Bone Regency. The research method used is descriptive quantitative research and population in this study were all honorary teachers who tought the at the school with a sample of 16 honorary teachers. Research instruments using questionnaires and documentation. The data analysis technique used is descriptive analysis with the product moment statistical test. Based on the results of data analysis using descriptive statistics, it is known that the average value for compensation (X) is 16, number 16 is in the sufficient category and the average value for the performance of honorary teachers (Y) is 52,25, number 52,25 is in the good category. While the results of the statistical analysis of the product moment show the regression test results obtained bythe value095, this proves that the provision of compensation for the performance of honorary teachers is relatively strong. Then used the F statistic with the criteria for rejecting test, if Font Frable with a value 12,36-4,60. This shows that there is a positive and significant effect between the provision of compensation to the improvement of the performance of honorary teachers in SMPN 3 Awangpone District Bone Regency.